Determination of γ-oryzanol, Phenolic total content, and (2,2-difenil-1-picrylhydrazyl) Radical Scavenging Activity in Different Varieties of Rice (Oryza sativa) in Yogyakarta, Indonesia - Erna Prawita Setyowati; Andayana Puspitasari Gani (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
In Indonesia, beras (Oryza sativa) has become the main ingredient in natural beauty products such as masks, scrubs, and cold powder. γ-oryzanol and phenolic compounds are the major components in beras that have many benefits, one of which as antioxidants. This study aims to determine the content of γ-oryzanol and total phenolic compounds in different beras cultivars in the area of Yogyakarta. The leveling was done by a TLC-densitometry method and Folin Ciocalteu. The results showed that the largest γ-oryzanol content found in red beras was 0.0843% by weight of the sample. The highest total phenolic content was found in red beras as much as 1.92% by weight of the sample. The antioxidants activity IC50 Red Beras is 0.591.